Regional-scale paleofluid system across the Tuscan Nappe-Umbria-Marche Apennine Ridge (northern Apennines) as revealed by mesostructural and isotopic analyses of stylolite-vein networks - Beaudoin, Nicolas E.; Labeur, Aurelie; Lacombe, Olivier; Köhn, Daniel; Billi, Andrea; Hoareau, Guilhem; Boyce, Adrian; John, Cedric M.; Marchegiano, Marta; Roberts, Nick M.; Millar, Ian L.; Claverie, Fanny; et al. (Solid Earth, 2020)
We report the results of a multiproxy study that combines structural analysis of a fracture-stylolite network and isotopic characterization of calcite vein cements and/or fault coating. Together with new paleopiezometric and radiometric constraints on burial evolution and deformation timing, these results provide a first-order picture of the regional fluid systems and pathways that were present during the main stages of contraction in the Tuscan Nappe and Umbria-Marche Apennine Ridge (northern Apennines). We reconstruct four steps of deformation at the scale of the belt: burial-related stylolitization, Apenninic-related layer-parallel shortening with a contraction trending NE-SW, local extension related to folding, and late-stage fold tightening under a contraction still striking NE-SW. We combine the paleopiezometric inversion of the roughness of sedimentary stylolites - that constrains the range of burial depth of strata prior to layer-parallel shortening - with burial models and U-Pb absolute dating of fault coatings in order to determine the timing of development of mesostructures. In the western part of the ridge, layer-parallel shortening started in Langhian time (similar to 15 Ma), and then folding started at Tortonian time (similar to 8 Ma); late-stage fold tightening started by the early Pliocene (similar to 5 Ma) and likely lasted until recent/modern extension occurred (similar to 3 Ma onward). The textural and geochemical (delta O-18, delta C-13, Delta 47CO2 and Sr-87/Sr-86) study of calcite vein cements and fault coatings reveals that most of the fluids involved in the belt during deformation either are local or flowed laterally from the same reservoir. However, the western edge of the ridge recorded pulses of eastward migration of hydrothermal fluids (>140 degrees C), driven by the tectonic contraction and by the difference in structural style of the subsurface between the eastern Tuscan Nappe and the Umbria-Marche Apennine Ridge.
CRIS-Team WoS Importer:2020-09-25